Analysis of Conflicts and Delays of Cyclists, Vehicles, and Pedestrians at a Busy Intersection in Lima Downtown, Peru - Silva, Jose (2023)
In Lima downtown, highly congested intersections with many cyclists and pedestrians can be observed, where conflicts are very common. Therefore, it is important to reduce conflicts to improve the mobility of all users at intersections. At the intersection of Garcilaso de la Vega and 9 de Diciembre avenues, located in the center of Lima, the behavior of the users was observed, especially that of the cyclists, where the spontaneous routes they have adapted to cross the intersection more quickly were visualized. In this study, two scenarios were evaluated: The first scenario used the current fixed traffic light cycle as the geometry of the location, and it also represented how cyclists cross through unplanned routes. In contrast, the second scenario involved adaptive traffic lights and formalized two routes for cyclists, allowing them to choose more than one alternative depending on the phase they are in when crossing the intersection. The Vissim software was used for modeling, and the SSAM methodology was employed for comparison, which counted the number of conflicts. As a result, the second scenario showed 18% fewer conflicts among users. Additionally, cyclists experienced 18% less delay.